2019
DOI: 10.1051/0004-6361/201935849
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent weak friction model for the tidal evolution of circumbinary planets

Abstract: We present a self-consistent model for the tidal evolution of circumbinary planets that is easily extensible to any other three-body problem. Based on the weak-friction model, we derive expressions of the resulting forces and torques considering complete tidal interactions between all the bodies of the system. Although the tidal deformation suffered by each extended mass must take into account the combined gravitational effects of the other two bodies, the only tidal forces that have a net effect on the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(46 citation statements)
references
References 19 publications
6
39
1
Order By: Relevance
“…It may also be possible to reduce the binary eccentricity through tidal interaction with the planet after the disc has been dispersed. Thereby, the low eccentric binaries may have been more eccentric during the planet formation phase and only lost the eccentricity after the planets reached stable orbits and were thus undisturbed by the outer disc (Zoppetti et al 2019).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…It may also be possible to reduce the binary eccentricity through tidal interaction with the planet after the disc has been dispersed. Thereby, the low eccentric binaries may have been more eccentric during the planet formation phase and only lost the eccentricity after the planets reached stable orbits and were thus undisturbed by the outer disc (Zoppetti et al 2019).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In Zoppetti et al (2019) we presented a self-consistent tidal model for the planar and non-oblique 3BP, using a weak friction Constant Time Lag (CTL) model based on the expressions of the tidal forces and torques of the classical work of Mignard (1979). We applied the model to the circumbinary (CB) case and found that for systems like those discovered by the Kepler mission, the planet acquired stationary spin rates on timescales of approximately millions of years (depending on the dissipation factor Q 2 ) and, curiously, in subsynchronous solutions (Zoppetti et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We focused our habitability analysis on orbital evolution, but many other factors might be important and could be included in future work. CBP rotation rates may reach a stationary solution analogous to tidal locking (Zoppetti et al 2019;Zoppetti et al 2020), which could significantly affect climates (see e.g., Pierrehumbert 2011;Yang et al 2013;Del Genio et al 2019). The planets of M dwarf stars, such as those in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Fleming et al (2018) dubbed their model the "Stellar-Tidal Evolution Ejection of Planets" (STEEP). We note that Zoppetti et al (2019) showed that outward-then-inward evolution of the binary orbit can occur even when one ignores the stellar evolution.…”
Section: Introductionmentioning
confidence: 88%